2014
DOI: 10.1017/s1368980014002572
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of folic acid-fortified foods to fertile women’s folate Recommended Nutrient Intake through breakfast simulation models

Abstract: At existing levels of FA fortification, inclusion of fortified products as part of a regular breakfast meal could positively impact the nutritional quality of women's diet without involving a risk of excessive FA exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
(33 reference statements)
0
5
0
Order By: Relevance
“…The relative high micronutrient intakes at breakfast observed in the current study are likely to be at least partially driven by current Spanish voluntary fortification practices (mainly in milk and milk products and cereals), although a tendency to decrease the presence of fortified foods (e.g., calcium and folic acid) in the Spanish market in the last years has been reported [ 37 , 38 ]. Notably, fortified breakfast cereal consumption has been associated with a higher dietary adequacy, specifically in relation to B vitamins, vitamin D and iron, without the risk of exceeding the Tolerable Upper Intake Level intake [ 39 ] and also towards a better nutrient-dense breakfast model in Spain [ 40 ]. The contribution of total fats and monounsaturated fatty acids from breakfast are also below the thresholds when compared to the daily energy, particularly for polyunsaturated fatty acids (PUFA).…”
Section: Discussionmentioning
confidence: 99%
“…The relative high micronutrient intakes at breakfast observed in the current study are likely to be at least partially driven by current Spanish voluntary fortification practices (mainly in milk and milk products and cereals), although a tendency to decrease the presence of fortified foods (e.g., calcium and folic acid) in the Spanish market in the last years has been reported [ 37 , 38 ]. Notably, fortified breakfast cereal consumption has been associated with a higher dietary adequacy, specifically in relation to B vitamins, vitamin D and iron, without the risk of exceeding the Tolerable Upper Intake Level intake [ 39 ] and also towards a better nutrient-dense breakfast model in Spain [ 40 ]. The contribution of total fats and monounsaturated fatty acids from breakfast are also below the thresholds when compared to the daily energy, particularly for polyunsaturated fatty acids (PUFA).…”
Section: Discussionmentioning
confidence: 99%
“…This study also found that the use of antibiotics before or early pregnancy was associated with NTDs. The possible reason is that antibiotic medications may have antifolate effects [ 86 ]. Some specific forms of antibiotics such as sulfonamides are risk for fetus developing NTDs [ 87 , 88 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Spain, women of childbearing age are at risk of insufficient folate intakes since only 50% of recommended folate intake is ingested through diet at present [10]. The daily inclusion of fortified products could provide this population group with 20%–60% of FA recommended intake, when fortification level 4 products are consumed [31]. On the other hand, there is concern that population subgroups, including children and the elderly, may be at risk of consuming usual intakes above the UL.…”
Section: Discussionmentioning
confidence: 99%
“…Data is scarce and therefore quantification of the underestimation of FA intake due to the non-consideration of fortified products is still speculative. According to our previous studies, the non-consideration of FA fortification may underestimate as much as 40% of actual folate and folic acid intake in women [31] and children [32]. In the Irish study [22] the difference in total folate and FA intake between consumers and non-consumers of fortified products is above 50%.…”
Section: Discussionmentioning
confidence: 99%